Fe-rich rare earth-poor SmFe12-based nanocrystalline permanent magnet alloy block material and preparation method thereof

Through the technical route of combining high-energy ball milling, rapid hot press sintering and quenching heat treatment, combined with element doping and amorphous crystallization, a stable SmFe12-based nanocrystalline alloy bulk material was prepared, solving the problems of instability and difficulty in synthesis of SmFe12 compounds and improving its coercive force and magnetic properties.

CN119889852APending Publication Date: 2025-04-25BEIJING UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510080233.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The SmFe12 compound is unstable and difficult to synthesize, resulting in its excellent intrinsic magnetic properties that cannot be converted into high coercive forces, limiting its application in permanent magnet materials.

Method used

Using a combination of high-energy ball milling, rapid hot press sintering and quenching heat treatment, a stable SmFe12-based nanocrystalline alloy bulk material is prepared through element doping and amorphous crystallization.

Benefits of technology

The technical difficulties in the preparation of SmFe12-based alloy bulk material were successfully solved, and SmFe12-based nanocrystalline permanent magnet alloy bulk material with a 1:12 main phase and controllable nanoscale grain size was obtained, which improved its coercive force and magnetic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119889852A_ABST
    Figure CN119889852A_ABST
Patent Text Reader

Abstract

The invention discloses a Fe-rich rare earth-poor SmFe12-based nanocrystalline permanent magnet alloy block material and a preparation method thereof, and belongs to the technical field of powder metallurgy. The preparation method comprises the following steps: proportioning a metal Sm block, a metal Fe block and a doping element M (metal elements of Ti, V and Mn) small block according to a molar ratio of Sm: (Fe + M) of 1: 12, wherein the mass ratio of Sm is theoretically increased by 20-25% during proportioning; smelting by using a magnetic suspension induction smelting furnace to obtain a master alloy ingot with the nominal composition of SmFe12-xMx (x = 0-2); crushing the mother alloy ingot into powder particles in a glove box under argon protection, and putting the powder particles into a ball milling tank under argon protection for ball milling to prepare amorphous alloy powder; amorphous alloy powder is put into a hard alloy mold to be pre-pressed, then nanocrystalline bulk alloy is prepared through rapid hot pressing sintering forming, and finally the grain size and the microstructure of the alloy are regulated and controlled through quenching heat treatment. The main phase of the prepared material is 1: 12, the grain size is controllable in nanoscale, and the process route is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a technical route combining high-energy ball milling, rapid hot pressing sintering and quenching heat treatment to prepare Fe-rich rare earth-poor SmFe by element doping, amorphous crystallization and heat treatment. 12 The invention discloses a method for preparing a nanocrystalline permanent magnet alloy block material, belonging to the technical field of rare earth permanent magnet alloy and powder metallurgy. Background Art

[0002] With the development of "green technology" and the increasing demand for rare earth resources, the research on rare earth-poor permanent magnet alloys has received more and more attention. 12 The 1:12 type rare earth-transition metal compounds with a type crystal structure are considered to be the most promising rare earth-poor permanent magnet materials. Tetragonal ThMn with strong uniaxial anisotropy 12 SmFe 12 The base permanent magnet compound has excellent intrinsic magnetic properties μ0Ms=1.64T and μ0Ha=12T, and the rare earth element Sm accounts for 7.7%, which is the lowest among permanent magnet materials. 12 The base alloy is rich in iron and is not affected by the strategic resource Co, making it one of the strong candidates for new permanent magnet materials. 12 The phase is a metastable phase that cannot exist stably in the form of a block at room temperature, and its excellent intrinsic magnetic properties cannot be converted into high coercivity. 12 Base alloys are of great significance for the development of new permanent magnetic materials.

[0003] In order to obtain a stable SmFe 12 Phase, doping with a certain amount of stabilizing elements is a necessary means. In addition, nanocrystalline alloys usually have higher coercivity than traditional coarse-grained alloys. The amorphous crystallization method is widely used in the research of nanomaterials. Based on the single domain theory of magnetic materials, the nanoscale grains produced by crystallization are conducive to the grain size of permanent magnetic alloys close to the single domain size, which helps to improve the coercivity of the alloy. At the same time, grain size nanosizing can obtain metastable phases that are difficult to exist in certain traditional coarse-grained alloys. Heat treatment can regulate the grain size and microstructure of the alloy, further ensure the uniform distribution of phases and grain sizes, eliminate crystal defects, and help improve magnetic properties.

[0004] The present invention prepares SmFe based on a method of amorphous crystallization, element doping and heat treatment. 12 Based on nanocrystalline alloy bulk material, the preparation route of this technology is highly controllable, the alloy grain size is small and the microstructure is uniform. Summary of the invention

[0005] The present invention is directed to SmFe 12The compounds are unstable and difficult to synthesize, and a Fe-rich rare earth-poor SmFe 12 Preparation method of nanocrystalline permanent magnet alloy bulk material based on SmFe 12 Nanocrystalline alloy bulk material with nanocrystalline alloy as the main phase.

[0006] The Fe-rich rare earth-poor SmFe 12 The preparation method of the nanocrystalline permanent magnetic alloy bulk material is characterized by comprising the following steps:

[0007] (1) Weigh the metal Sm block, metal Fe block and small pieces of added element M (Ti, V, Mn metal elements) according to the molar ratio of Sm:Fe:M=1:(12-x):x. M can be one or more metals with a total amount of x=0-2. In order to compensate for the volatilization loss of Sm during the smelting process, the mass ratio of Sm is increased by 20%-25% to the theoretical value when the raw materials are proportioned. First, spread the high-melting-point Fe block and small pieces of doping elements around the inner wall of the crucible, and then put the low-melting-point Sm block into the middle area surrounded by the Fe block and small pieces of doping elements. This charging method can reduce the volatilization loss of Sm and increase the composition uniformity of the ingot obtained by smelting. Use a magnetic levitation induction melting furnace to melt the Sm, Fe and doping element M raw materials. Before smelting, reduce the vacuum degree in the furnace to 10 -2 Pa, the melting duration is 300-350s, and the ingot is melted 3-4 times. Each time the ingot is remelted, the upper and lower surfaces are turned over and placed in the crucible to enhance the uniformity of the composition and obtain SmFe 12-x M x Master alloy ingot;

[0008] (2) SmFe obtained by smelting 12-x M x Grind off the surface layer of the master alloy ingot. In a glove box protected by argon (99.999%) atmosphere, crush the ingot into powder particles. Load the grinding balls and powder particles into the ball mill at a ball-to-material mass ratio of 15:1-20:1. The rotation speed during ball milling is 400-500r / min, and the machine is stopped for 0.5h for every 1h of continuous ball milling. Reasonable optimization of the above ball milling process can take into account the preparation efficiency while avoiding overheating of the ball milling system that may cause phase change or oxidation of the material. Scrape and sieve powder in a glove box protected by argon (99.999%), and obtain alloy powder with an amorphous structure after 4-6h of ball milling;

[0009] (3) The amorphous powder obtained by ball milling is loaded into a cemented carbide mold under the protection of argon (99.999%) and pre-pressed with a pressure of 50-100 MPa, and then sent to a rapid hot pressing sintering equipment for sintering and densification. The specific process parameters are as follows: sintering temperature is 600-680°C, heating rate is 30-50°C / min, holding time is 1-5min, and sintering pressure is 400-600 MPa;

[0010] (4) The sintered bulk alloy was further heat treated in a box furnace. In order to prevent oxidation of the sample during the heat treatment, the sample was sealed in a quartz tube under an argon (99.999%) atmosphere before the heat treatment. The argon pressure in the quartz tube was 0.2 atmospheres. The heat treatment process parameters were as follows: the heating rate of the heat treatment was 5-10°C / min, the holding temperature was 600-800°C, the holding time was 5-15min, and the quenching was carried out with water as the medium. After the heat treatment, SmFe 12 Based nanocrystalline alloy bulk.

[0011] The present invention utilizes a technical route combining high-energy ball milling, rapid hot pressing sintering and quenching heat treatment, and a technical means of producing a nanocrystalline alloy within a certain grain size range by element doping and crystallization of amorphous alloy powder to prepare a stable SmFe 12 Based on nanocrystalline alloy bulk materials. It solves the problem of Fe-rich rare earth-poor nanocrystalline SmFe 12 The present invention solves the technical difficulties in preparing bulk alloy materials and provides a preparation technology with a phase composition of 1:12 main phase, controllable grain size at the nanoscale, and a simple process route. The present invention has the following characteristics and advantages:

[0012] (1) The powder loading, ball milling, scraping and sieving operations are carried out under argon protection to ensure that the ball milled powder is not oxidized and contaminated. (2) The high-energy ball milling method can obtain amorphous powder, which will crystallize during the subsequent sintering process to obtain nano-scale grains. (3) Using rapid hot pressing sintering technology, high-pressure and rapid sintering can produce dense SmFe with nano-scale grain size. 12 Based on nanocrystalline alloy bulk materials. (4) The grain size and microstructure of the alloy can be regulated by quenching heat treatment, further ensuring the uniform distribution of phases and grain size. (5) The process of multiple magnetic levitation induction melting, high-energy ball milling, rapid hot pressing sintering and quenching heat treatment ensures the uniform distribution of doping elements. This process can be extended to multiple doping elements to regulate the magnetic properties of the prepared alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 The nominal composition obtained by smelting in Example 1 is SmFe 11 X-ray diffraction pattern of Ti1 master alloy ingot.

[0014] Figure 2 The nominal composition obtained by smelting in Example 1 is SmFe 11 Backscattered electron image of Ti1 master alloy ingot.

[0015] Figure 3 The nominal composition obtained by smelting in Example 1 is SmFe 11 Amorphous alloy powder (a) obtained by ball milling Ti1 master alloy ingot and SmFe 12 X-ray diffraction pattern of the bulk nanocrystalline alloy (b).

[0016] Figure 4 The nominal composition obtained by smelting in Example 1 is SmFe 11 SmFe 12 Transmission electron microscope bright field image (a) and the corresponding selected area electron diffraction spectrum (b) of the nanocrystalline alloy bulk.

[0017] Figure 5 The nominal composition obtained by smelting in Example 1 is SmFe 11 SmFe Ti1 master alloy ingot was prepared by ball milling, rapid hot pressing sintering and quenching heat treatment. 12 X-ray diffraction pattern of the bulk nanocrystalline alloy. Figure 6 The nominal composition obtained by smelting in Example 1 is SmFe 11 SmFe Ti1 master alloy ingot was prepared by ball milling, rapid hot pressing sintering and quenching heat treatment. 12 Transmission electron microscope bright field image (a) and the corresponding selected area electron diffraction spectrum (b) of the nanocrystalline alloy bulk.

[0018] Figure 7 The nominal composition obtained by smelting in Example 2 is SmFe 10 SmFe was prepared by ball milling and rapid hot pressing sintering of Ti1Mn1 master alloy ingots. 12 X-ray diffraction pattern of the bulk nanocrystalline alloy.

[0019] Figure 8 The nominal composition obtained by smelting in Example 2 is SmFe 10 SmFe 12 X-ray diffraction pattern of the bulk nanocrystalline alloy.

[0020] Fig. 9 The nominal composition obtained by smelting in Example 2 is SmFe 10SmFe 12 Transmission electron microscope bright field image of the bulk of the nanocrystalline alloy.

[0021] Fig.10 The nominal composition obtained by smelting in Example 3 is SmFe 10 Ti1V 0.5 The master alloy ingot was prepared by ball milling, rapid hot pressing sintering and quenching heat treatment. 12 X-ray diffraction pattern of the bulk nanocrystalline alloy. DETAILED DESCRIPTION

[0022] The present invention is further explained by the following examples, but the present invention is not limited to the following examples.

[0023] Example 1

[0024] The single substance Fe block, Sm block and doped element Ti block are used as raw materials, which are cut into small pieces and placed in a magnetic suspension induction melting furnace according to the molar ratio of Sm:Fe:Ti=1:11:1. The mass ratio of Sm is increased by 25% compared with the theoretical value. -2 The smelting was carried out below Pa, the smelting time was 300s, and after remelting 4 times, a master alloy ingot with uniform composition was obtained.

[0025] The master alloy ingot was mechanically crushed into powder particles and loaded into a ball mill filled with argon (99.999%), with a ball-to-material ratio of 20:1, a rotation speed of 500 r / min, a ball milling time of 4 h, and a pause of more than 0.5 h after every 1 h of operation to obtain amorphous alloy powder.

[0026] The amorphous alloy powder was loaded into a cemented carbide mold and pre-pressed under a pressure of 64 MPa to prepare nanocrystalline SmFe by rapid hot pressing and sintering. 12 The base alloy was heated at a rate of 50°C / min, sintered at 680°C, held for 1 min, and kept at a constant pressure of 500 MPa to obtain nanocrystalline SmFe 12 The main phase of the base alloy is SmFe 12 , the average grain size is 23.5nm.

[0027] The sintered bulk alloy was sealed in an argon (99.999%) atmosphere, and then further quenched at a heating rate of 10°C / min, a holding temperature of 800°C, and a holding time of 15 min to obtain nanocrystalline SmFe 12 The main phase of the base alloy is SmFe 12 , the average grain size is 34.4nm.

[0028] The nominal composition obtained by smelting in Example 1 is SmFe11 Phase analysis of Ti1 master alloy ingot is shown in Figure 1 , SmFe 11 The master alloy ingot of Ti1 is composed of SmFe 12 and α-Fe, of which the metastable phase SmFe 12 The main phase, α-Fe phase content is very low. SmFe 11 The backscattered electron image of the master alloy ingot of Ti1 is shown in Figure 2 , it can be seen that the backscattered electron image has two kinds of contrast. Through the energy spectrum analysis, it can be known that the gray contrast area is SmFe 12 Phase, the black contrast area is α-Fe phase, and the grain size is micron-level. This shows that SmFe 12 The main phase, but the nanocrystalline structure cannot be obtained.

[0029] Phase analysis of the powder obtained by ball milling the alloy ingot is shown in Figure 3 (a) The spectrum contains only one main amorphous peak package, indicating that the alloy powder presents good amorphous characteristics. SmFe prepared by rapid hot pressing 12 Phase analysis of nanocrystalline alloy bulk is shown in Figure 3 (b), alloy composed of SmFe 12 and α-Fe phase, among which SmFe 12 The main phase is SmFe prepared by rapid hot pressing. 12 The microstructure of the nanocrystalline alloy bulk is shown in Figure 4 ,in Figure 4 (a) is a bright field image of a transmission electron microscope. Figure 4 (b) is the selected area electron diffraction spectrum. The average grain size is 23.5nm, with SmFe 12 The microstructure of the coexistence of SmFe 12 As the main phase.

[0030] The phase analysis of the alloy obtained by quenching heat treatment of the sintered block is shown in Figure 5 , although some SmFe 12 Phase decomposition into α-Fe and Sm2Fe 17 , but the SmFe 12 Still the main phase. SmFe after heat treatment 12 The microstructure of the nanocrystalline alloy bulk is shown in Figure 6 ,in Figure 6 (a) is a bright field image of a transmission electron microscope. Figure 6 (b) is the selected area electron diffraction spectrum. The average grain size is 34.4nm, with SmFe 12phase, α-Fe phase and Sm2Fe 17 Phase coexistence structure, SmFe 12 As the main phase, Sm2Fe 17 The phase exists in the form of fine precipitates.

[0031] Example 2

[0032] The single-substance Fe block, Sm block and doped element Ti and Mn block are used as raw materials, cut into small pieces, and placed in a magnetic suspension induction melting furnace according to the atomic ratio Sm:Fe:Ti:Mn=1:10:1:1. The mass ratio of Sm increases by 25% compared with the theoretical value. -2 The smelting was carried out below Pa, the smelting time was 320s, and after remelting 4 times, a master alloy ingot with uniform composition was obtained.

[0033] The master alloy ingot was mechanically crushed into powder particles and loaded into a ball mill filled with argon (99.999%), with a ball-to-material ratio of 20:1, a rotation speed of 450 r / min, a ball milling time of 6 h, and a pause of more than 0.5 h after every 1 h of operation to obtain amorphous alloy powder.

[0034] The amorphous alloy powder was loaded into a cemented carbide mold and pre-pressed with a pressure of 50 MPa. Nanocrystalline SmFe was prepared by rapid hot pressing and sintering. 12 The base alloy was heated at a rate of 45°C / min, sintered at 650°C, kept warm for 5 min, and kept at a constant pressure of 500 MPa to obtain a main phase of SmFe 12 The nanocrystalline alloy has an average grain size of 21.2nm.

[0035] The sintered bulk alloy was sealed in an argon (99.999%) atmosphere, and then further quenched at a heating rate of 10°C / min, a holding temperature of 800°C, and a holding time of 10 min to obtain nanocrystalline SmFe 12 The main phase of the base alloy is SmFe 12 , the average grain size is 32.8nm.

[0036] The nominal composition obtained by smelting in Example 2 is SmFe 10 SmFe prepared by ball milling and rapid hot pressing sintering of Ti1Mn1 master alloy ingot 12 Phase analysis of nanocrystalline alloy bulk is shown in Figure 7 , by SmFe 12 and α-Fe phase, among which SmFe 12 It is the main phase and contains only a small amount of α-Fe phase.

[0037] The phase analysis of the alloy obtained by quenching heat treatment of the sintered block is shown in Figure 8Although the proportion of α-Fe phase increases, the SmFe 12 Still the main phase. SmFe after heat treatment 12 Transmission electron microscope bright field image of the nanocrystalline alloy bulk Fig. 9 ,The microstructure morphology shows that the grain size is uniformly distributed, and the average grain size is 32.8nm.

[0038] Example 3

[0039] The single substance Fe block, Sm block and doping element Ti, V block are used as raw materials, cut into small pieces, and placed in a magnetic suspension induction melting furnace according to the molar ratio of Sm:Fe:Ti:V=1:10.5:1:0.5. The mass ratio of Sm is increased by 20% compared with the theoretical value. -2 The smelting was carried out below Pa, the smelting time was 350s, and after remelting three times, a master alloy ingot with uniform composition was obtained.

[0040] The master alloy ingot was mechanically broken into powder particles and loaded into a ball mill filled with argon (99.999%), with a ball-to-material ratio of 20:1, a rotation speed of 400 r / min, a ball milling time of 5 h, and a pause of more than 0.5 h after every 1 h of operation to obtain amorphous alloy powder.

[0041] The amorphous alloy powder was loaded into a cemented carbide mold and pre-pressed with a pressure of 100 MPa. Nanocrystalline SmFe 12 The main phase of the alloy was SmFe, the heating rate was 40℃ / min, the sintering temperature was 650℃, the temperature was kept for 3min, and the constant pressure was 450MPa. 12 The nanocrystalline alloy has an average grain size of 22.3nm.

[0042] The sintered bulk alloy was sealed in an argon (99.999%) atmosphere, and then further quenched at a heating rate of 10°C / min, a holding temperature of 600°C, and a holding time of 5 min to obtain nanocrystalline SmFe 12 The main phase of the base alloy is SmFe 12 , the average grain size is 30.4nm.

[0043] The nominal composition obtained by smelting in Example 3 is SmFe 10.5 Ti1V 0.5 SmFe2O3 was prepared by ball milling, rapid hot pressing sintering and quenching heat treatment of master alloy ingot. 12 Phase analysis of nanocrystalline alloy bulk is shown in Fig.10 , by SmFe 12 and α-Fe phase, among which SmFe 12 It is the main phase and contains only a small amount of α-Fe phase.

Claims

1. A Fe-rich rare earth-poor SmFe 12 The method for preparing a nanocrystalline permanent magnet alloy bulk material is characterized in that: The following steps are involved: (1) weighing a metal Sm block, a metal Fe block and a small piece of doping element M according to a molar ratio of Sm:Fe:M=1:(12-x):x, where x is less than or equal to 2; in order to compensate for the volatilization loss of Sm during the smelting process, the mass ratio of Sm is increased by 20%-25% of the theoretical value when the raw materials are proportioned; firstly spreading a high melting point Fe block and a small piece of doping element around the inner wall of the crucible, and then placing a low melting point Sm block in the middle area surrounded by the Fe block and the small piece of doping element; using a magnetic levitation induction melting furnace to melt the Sm, Fe and doping element M raw materials; before melting, reducing the vacuum degree in the furnace to 10 -2 Pa, the smelting time is 300-350s; after smelting to obtain the ingot, it is smelted 3-4 times to obtain SmFe with uniform composition. 12-x M x Master alloy ingot; (2) SmFe obtained by smelting 12-x M x The surface layer of the master alloy ingot is ground off; in a glove box protected by an argon atmosphere, the ingot is crushed into powder particles, and the grinding balls and the powder particles are loaded into a ball mill according to a ball-to-material mass ratio of 15:1-20:1; (3) The amorphous powder obtained by ball milling is loaded into a cemented carbide mold under argon protection and pre-pressed with a pressure of 50-100 MPa, and then sent to a rapid hot pressing sintering equipment for sintering and densification; the sintering temperature is 600-680°C, the heating rate is 30-50°C / min, the holding time is 1-5min, and the sintering pressure is 400-600 MPa; (4) The sintered bulk alloy is further heat treated in a box furnace. The heat treatment conditions are a heating rate of 5-10°C / min, a holding temperature of 600-800°C, and a holding time of 5-15min. The alloy is quenched in water. After heat treatment, SmFe 12 Based nanocrystalline alloy bulk.

2. The method according to claim 1, characterized in that The doping elements that can be used in the step (1) include one or more of Ti, V, and Mn metals.

3. The method according to claim 1, characterized in that The specific process parameters of the ball milling in step (2) are as follows: the rotation speed during ball milling is 400-500 r / min, and the machine is stopped for more than 0.5 h for every 1 h of continuous ball milling; the powder scraping and sieving operations are performed in an argon-protected glove box, and an amorphous alloy powder is obtained after ball milling for 4-6 h.

4. The method according to claim 1, characterized in that Step (4) In order to prevent the sample from being oxidized during the heat treatment, the sample is sealed in a quartz tube under an argon atmosphere before the heat treatment.

5. SmFe prepared according to the method according to any one of claims 1 to 4 12 Based nanocrystalline alloy bulk materials.